Evaluation of the effectiveness of active vitamin d use in experimental rat lymphedema model - Aksöyler, Dicle; Kozanoğlu, Erol; Korkut, Mehmet; Akpınar, Ömer Faruk; Çaylı, Muhammet; Özdemir, İlkay; Losco, Luigi (My University, 2024)
Background and Objectives: Lymphedema is a progressive, chronic condition. Traumatic damage to the lymphatics, removal of lymph nodes, and/or radiation are the major causes of fibrosis and a subsequent pathological cascade. Macrophages play a crucial role in wound healing, with M1 macrophages known for their pro-inflammatory effects and M2 macrophages recognized for their anti-inflammatory effects, including improved angiogenesis, lymph angiogenesis, and tissue healing. This study aims to assess the use of calcitriol to alter the M2/M1 macrophage balance, reduce tissue fibrosis in a lymphedema model, promote new micro-lymphatic vessel formation, and evaluate the benefits of active vitamin D. Material and Methods: Forty-five rats were randomly divided into three groups: control surgery (group A), surgery with preoperative–postoperative calcitriol (group B), and postoperative calcitriol (group C). One week after the surgical ablation a total dose of 20 Gy radiation therapy was administered to the operated groin region. Micro-computed tomography was used for limb volume calculation, fluorescence lymphatic imaging was used to assess the presence of lymphedema, and histopathological analyses were conducted to evaluate the M1/M2 macrophage ratio, fibrosis accumulation, and lymph angiogenesis. Results: The micro-computed tomography evaluation revealed that 75% of the rats of group A exhibited long-lasting lymphedema. In group B, the initial lymphedema ratio was the lowest, affecting only 25% of the rats. After ligating the main vessels, a linear lymphatic microvascular structure was observed in groups B and C. Group B had a significant increase in M2 macrophages and newly formed lymphatic vessels (p < 0.05). However, group A showed a significant elevation of M1 macrophages and collagen accumulation (p < 0.05) in the surgically treated hind limb. Conclusions: Both histological analyses and clinical results reported a relevant influence of calcitriol administration. Among all groups, the most favorable outcomes were seen in group B (prophylaxis group). Hence, calcitriol administration could play a crucial role in enhancing the migration of M2 macrophages to the damaged tissue. Such migration may contribute to lymphedema resolution either by enhancing the organization of superficial lymphatic vessels or resolving fibrosis, or with a combination of both these mechanisms.
Keywords: Active Vitamin D; Fibrosis; Lymphangiogenesis; Lymphedema Rat Model; M1 Macrophages; M2 Macrophages; M2/M1 Macrophage Balance